PENYUSUNAN BAHAN AJAR PENGAYAAN BERDASARKAN KURIKULUM 2013 DAN PENDIDIKAN KARAKTER BAHASA ARAB MADRASAH IBTIDAIYAH - Zukhaira, Zukhaira; Hasyim, Mohamad Yusuf A. (Universitas Negeri Semarang, 2014)
This activity was conducted in order to explain the importance and purpose and benefits of the preparation of teaching materials based on the enrichment of the Arabic language and character education curriculum in 2013, describes the steps the preparation of teaching materials based on the enrichment of Arabic language, and the ability of teachers to develop language Arab Elementary School as the city of Semarang in preparing teaching materials based Arabic language enrichment and character education curriculum in 2013 and can apply them in the teaching and learning Arabic at Government Elementary School , respectively . Alternative solutions that have been implemented are providing education and training. The conclusions of this activity is that the implementation of the community service is very useful for the target audience in this case Arabic teachers Elementary School as the city of Semarang . With this training teachers of Arabic as Semarang MI can arrange teaching materials based on the enrichment of the Arabic language and character education curriculum in 2013 to improve the quality of Arabic learning and apply it in teaching and learning activities at the school, respectively.